High performance nano-scale measurements by advanced atomic force estimation - Cui, Song (2011)
Atomic force microscopy (AFM) was invented by G. Binnig and his collaborators in 1986 after the invention of scanning tunnelling microscopy (STM) in the early 1980s. The AFM system deploys a tiny probe to interact with the sample such that topography information of the sample can be obtained. The resolutions of the AFM topography images are in the nanometer scale and they are limited only by the probe diameters. Besides, in AFM imaging, there is no requirement on sample preparation and conductivity. Thus, the AFM provides an easy platform to observe, measure and manipulate atomic interactions. Since its invention, AFM has become an indispensable tool in the research areas of material sciences and biological sciences. The AFM is also widely used in many industry applications in microelectronics and data storage. Although many research areas and industry applications have benefited from the success of AFM, there is still an urgent need to improve the measurement resolution and accuracy of the AFM in order to further exploit the atomic characteristics at the scales of atoms or even smaller. In addition, AFM has been modified as a Casimir oscillator to study quantum fluctuations where highly accurate and precise measurement is also desired. Driven by this motivation, this thesis will focus on the improvement of accuracy and resolution of the AFM and its modified system, the Casimir oscillator.